Synthesis and Structural Studies of Mn(II) and Zn(II) Thiazole–Schiff Base Complexes with Catalytic Application in Benzyl Alcohol Oxidation: Structural studies and catalytic applications of novel Mn(II) and Zn(II) metal complexes (Indian Journal of Chemistry (IJC), 2026)
Manganese(II) and zinc(II) Schiff base complexes derived from salicylaldehyde and ethyl 2-(2-amino-1,3-thiazol-4-yl)acetate were synthesized and characterized using elemental analyses, IR and UV–Vis spectroscopy. Their catalytic activities were assessed for the selective oxidation of benzyl alcohol employing hydrogen peroxide as a green oxidant under mild conditions. The gas chromatographic study identified benzaldehyde as the primary product, while benzoic acid and benzyl benzoate as minor by-products. The manganese complex exhibited the superior catalytic activity, (approximately 95% selectivity) due to its redox versatility and enhanced electron-transfer capability. The study demonstrated that optimization of parameters such as reaction time, temperature, H₂O₂ concentration, catalyst loading, and catalyst type significantly influenced both selectivity and conversion. With a selectivity of approximately 95%, this reaction is particularly promising for industrial applications in benzyl alcohol oxidation using environmentally benign catalysts.